Study on size and load rate effect of dynamic fragmentation and mechanical properties of marble sphere. (December 2022) - Zhao, Rui; Tao, Ming; Wu, Chengqing; Li, Xibing; Wang, Shaofeng
Highlights: 1) Dynamic load capacity of marble sphere was affected by size and impact velocity. 2) Hertz contact stress leads to the initial failure of the specimen. 3) The tensile-dominant cracks caused the overall damage of the specimen. 4) Paired-impact induced rock fragmentation depend on the velocity and block size. Abstract: Impact-induced fragmentation of rock blocks is a frequent phenomenon during rockfall, mining, geotechnical engineering. In order to obtain the fragmentation characteristics of rocks under the action of impact, the marble spheres with diameters of 30, 35, 40, 45, and 50 mm were used for paired-impact using the Split Hopkinson Pressure Bar (SHPB) tests, at the impact velocities of 4.5, 7.4 and 11.2 m/s, respectively, and the corresponding load and failure characteristics of each sample were examined. The experimental results revealed that the peak loading capacity and fragmentations of the rock sphere was influenced by the sample size and impact velocity. The finite element method (FEM) simulation by LS-DYNA was carried out to reveal the failure mechanism of marble spheres under paired-impact. Finally, a theoretical model was proposed to evaluating the breakage of rock block under impact. The results can be used to guide rock breakage in mines and rockfall hazard protection.